Human Resources Key Performance Indicators - Gabčanová Iveta (Journal of Competitiveness, 2012)
The article brings out a proposed strategy map and respective key performance indicators (KPIs) in human resources (HR). The article provides an overview of how HR activities are supported in order to reach the partial goals of HR as defined in the strategic map. Overall the aim of the paper is to show the possibilities of using the modern Balanced Scorecard method in human capital.